2017
DOI: 10.1111/cdev.12792
|View full text |Cite
|
Sign up to set email alerts
|

High School Dropout in Proximal Context: The Triggering Role of Stressful Life Events

Abstract: Adolescents who drop out of high school experience enduring negative consequences across many domains. Yet, the circumstances triggering their departure are poorly understood. This study examined the precipitating role of recent psychosocial stressors by comparing three groups of Canadian high school students (52% boys; M = 16.3 years; N = 545): recent dropouts, matched at-risk students who remain in school, and average students. Results indicate that in comparison with the two other groups, dropouts were over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 65 publications
(66 reference statements)
4
57
0
6
Order By: Relevance
“…For example, Dee and Penner [37], in a longitudinal study targeting those with GPA's under a 2.0, found that for 9th-grade students in an ethnic studies class, their attendance increased by 21%. While there are many reasons why students are absent from school, much is still unknown about the immediate triggers leading to leaving high school [38].…”
Section: Consequences Of Truancy Policies and Reasons For Absenteeismmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dee and Penner [37], in a longitudinal study targeting those with GPA's under a 2.0, found that for 9th-grade students in an ethnic studies class, their attendance increased by 21%. While there are many reasons why students are absent from school, much is still unknown about the immediate triggers leading to leaving high school [38].…”
Section: Consequences Of Truancy Policies and Reasons For Absenteeismmentioning
confidence: 99%
“…Pullout factors, such as poverty, domestic abuse, and violent neighborhoods, are rarely accounted for in the discussion of dropouts, and little is known about the immediate experiences that lead to students leaving high school [38]. Few scholars have accounted for how pullout factors encourage schools to generate pushout factors.…”
Section: The Current Studymentioning
confidence: 99%
“…The family is the framework in which the child's basic experiences are shaped and in which they are equipped with the main resources that enable them to deal with the educational framework and to benefit from it. The literature shows for example that families with low socioeconomic status constitute a catalyst for school dropout (Dupéré et al 2018). Families with many children, unemployed parents or low-income ones are associated with problems of dropout and low achievement (Ben-Rav & Kahan-Strawczynski, 2011).…”
Section: A Theoretical Frame For Educational Dropoutmentioning
confidence: 99%
“…The relationships among stigma, self-esteem, depression, and life satisfaction have been well documented as associated with dropping out of school and developmental outcomes [7,32,34,35]. However, the influence of a sense of (or perceived) stigma on health outcomes needs further attention regarding out-of-school youths in Korea.…”
Section: Introductionmentioning
confidence: 99%